Study of coronary artery calcium by multi-slice spiral CT as a tool for high risk cardiovascular screening - Gosavi, Rajesh V.; Holey, Madhuri P.; Giradkar, Umesh A. (International Journal of Research in Medical Sciences, 2017)
Background: Strong relationship has been demonstrated between the presence of occlusive CAD and coronary artery calcification (CAC) detected at autopsy, fluoroscopy and computed tomography (CT scan). CT scan quantifies the relative burden of CAC deposits as a marker of atherosclerosis. We explored utility of multi-slice spiral CT scan for detection of CAC as a tool for screening in asymptomatic high-risk cases above 40 years of age. Methods: Fifty-eight asymptomatic cardiovascular high-risk cases were included as per selection criteria. Detailed clinical history was recorded in every case regarding age, sex, history of risk factors for CAD like systemic hypertension, diabetes mellitus, smoking and family history of CAD. Every case was evaluated for fasting and postprandial blood sugar and fasting lipid profile. Body mass index (BMI) was calculated. An ECG was also recorded. Coronary artery calcium was estimated in each patient by multi -slice spiral CT scan. Fifty age and gender matched consenting participants were enrolled as controls and comparisons drawn. Results: Out of 58 cases scanned, 41 had no detectable CAC by multi-slice CT scan whereas in 17 cases (29.2%), calcium was detected. Mean CAC score was observed to increase as number of risk factors increased. Conclusions: Multi-slice CT scan is a useful tool for detection of coronary artery calcium (CAC) when utilised for high risk screening in older adults having one or more known cardiovascular risk factors.